Occurrence of ovarian follicular dominance during stimulation for ivm impacts usable blastocyst yield - Romero S. (2018)
The impact of the occurrence of ovarian focular dominance during hormonal stimulation for maturation in vitro is analyzed. This retrospective cohort study included 21 patients with polycystic ovaries or polycystic ovary syndrome (Rotterdam criteria, 2004) who underwent 24 cycles of in vitro maturation (IVM) between October 2015 and January 2017.